Eksplorasi Agens Hayati Rizoplan Sebagai Pengendali Jamur Fusarium oxysporum f.sp. cubense - I Gusti Made Wira Kesuma Jaya; Khamdan Khalimi; Ni Wayan Suniti (Fakultas Pertanian, Universitas Udayana, 2022)
Fusarium wild or wilt disease that attacks banana plants is caused by the pathogenic fungus Fusarium oxysporum f.sp. cubense This disease is difficult to control because it lasts a long time in the soil by forming chlamydospores. Currently, the control of this disease is still using synthetic fungicides, but this method can cause damage to the ecosystem. Biopesticide is one of the environmentally friendly control of plant pathogens because biopesticides use biological agents. The purpose of this study was to export rhizoplan bacteria from banana plant roots which have antifungal activity against F. oxysporum f.sp. cubense. The results showed that rhizoplan bacteria were able to inhibit the growth of Fusarium oxysporum f.sp. cubense fungal colonies on potato dextrose agar (PDA) media with an inhibitory percentage of 90.90% when compared to the control. The results of the bacterial filtrate test of rhizoplan at a concentration of 50% were able to inhibit the growth of the fungus Fusarium oxysporum f.sp. cubense with an inhibitory percentage of 92.72%.